Subjective facial analysis and its correlation with dental relationships - Gustavo Silva Siécola; Leopoldino Capelozza Filho; Diego Coelho Lorenzoni; Guilherme Janson; José Fernando Castanha Henriques
ABSTRACT INTRODUCTION: Subjective facial analysis is a diagnostic method that provides morphological analysis of the face. Thus, the aim of the present study was to compare the facial and dental diagnoses and investigate their relationship. METHODS: This sample consisted of 151 children (7 to 13 years old), without previous orthodontic treatment, analyzed by an orthodontist. Standardized extraoral and intraoral photographs were taken for the subjective facial classification according to Facial Pattern classification and occlusal analyses. It has been researched the occurrence of different Facial Patterns, the relationship between Facial Pattern classification in frontal and profile views, the relationship between Facial Patterns and Angle classification, and between anterior open bite and Long Face Pattern. RESULTS: Facial Pattern I was verified in 64.24% of the children, Pattern II in 21.29%, Pattern III in 6.62%, Long Face Pattern in 5.96% and Short Face Pattern in 1.99%. A substantial strength of agreement of approximately 84% between frontal and profile classification of Facial Pattern was observed (Kappa = 0.69). Agreement between the Angle classification and the Facial Pattern was seen in approximately 63% of the cases (Kappa = 0.27). Long Face Pattern did not present more open bite prevalence. CONCLUSION: Facial Patterns I and II were the most prevalent in children and the less prevalent was the Short Face Pattern. A significant concordance was observed between profile and frontal subjective facial analysis. There was slight concordance between the Facial Pattern and the sagittal dental relationships. The anterior open bite (AOB) was not significantly prevalent in any Facial Pattern.